SiO2@V2O5@Al2O3 core–shell catalysts with high activity and stability for methane oxidation to formaldehyde - Yang, Euiseob; Lee, Jun Gyeong; Kim, Dong Hyeon; Jung, Yoon Seok; Kwak, Ja Hun; Park, Eun Duck; An, Kwangjin (Journal of Catalysis, 2018)
The stable tetrahedral geometry and high C–H bond dissociation energy of methane complicate its direct catalytic conversion; for example, the selective oxidation of methane to formaldehyde, which avoids the production of carbon dioxide by full oxidation and is therefore important for the versatile utilization of natural gas, is still viewed as challenging. Here, we utilize hydrothermal synthesis followed by atomic layer deposition (ALD) to prepare an efficient and thermally stable catalyst based on novel SiO2@V2O5@Al2O3 core@shell nanostructures, showing that the thickness of Al2O3 shells over SiO2@V2O5 cores can be tuned by controlling the number of ALD cycles. Catalytic methane oxidation experiments performed in a flow reactor at 600 °C demonstrate that SiO2@V2O5@Al2O3 nanostructures obtained after 50 ALD cycles exhibit the best catalytic activity (methane conversion = 22.2%; formaldehyde selectivity = 57.8%) and outperform all previously reported vanadium-based catalysts at 600 °C. The prepared catalysts are subjected to in-depth characterization, which reveals that their Al2O3 shell provides new surfaces for the generation of highly disperse Td monomeric species with a V–O–Al bond by promoting interactions between Al2O3 and V2O5 nanoparticles during ALD. Moreover, the surface Al2O3 shell is found not only to protect V2O5 nanoparticles against sintering at 600 °C, but also to anchor the produced Td monomeric vanadium species responsible for the high catalytic performance.
Keywords: Catalytic conversion; Core shell; Core shell nano structures; High catalytic performance; Methane oxidation; Selective oxidation; Stable catalysts; Tetrahedral geometry; Core@shell; Formaldehyde; Methane oxidation; Stable catalyst; V2O5; Vanadium